Imaging of all three coronary arteries by transthoracic echocardiography. an illustrated guide - Krzanowski, Marek (BioMed Central, 2003)
BACKGROUND: Improvements in ultrasound technology has enabled direct, transthoracic visualization of long portions of coronary arteries : the left anterior descending (LAD), circumflex (Cx) and right coronary artery (RCA). Transthoracic measurements of coronary flow velocity were proved to be highly reproducible and correlated with invasive measurements. While clinical applications of transthoracic echocardiography (TTE) of principal coronary arteries are still very limited they will likely grow. The echocardiographers may therefore be interested to know the ultrasonic views, technique of examination and be aware where to look for coronary arteries and how to optimize the images. METHODS: A step-by-step approach to direct, transthoracic visualization of the LAD, Cx and RCA is presented. The technique of examination is discussed, correlations with basic coronary angiography views and heart anatomy are shown and extensively illustrated with photographs and movie-pictures. Hints concerning optimization of ultrasound images are presented and artifacts of imaging are discussed. CONCLUSIONS: Direct, transthoracic examination of the LAD, Cx and RCA in adults is possible and may become a useful adjunct to other methods of coronary artery examination but studies are needed to establish its role.